Pengaruh Terapi Butterfly Hug Terhadap Tingkat Kecemasan Dalam Penyusunan Skripsi Pada Mahasiswa Keperawatan Universitas Awal Bros - Loren Julia Simanjuntak; Utari Christya Wardhani; Yulianti Wulandari (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Students who always experience anxiety when writing their thesis often experience emotional mental disorders which can also be shown by symptoms of depression and anxiety. This research method uses pre-experiment, with a one group pre test - post test design approach without control group, with a sampling technique, namely purposive sampling. The data processed in this study used the paired T-Test. The results of the examination carried out before the butterfly hug therapy was given showed an average level of mild anxiety at a score of 47.30 and the results of the examination after being given butterfly hug therapy showed an average level of normal anxiety (not anxious) at a score of 31.90. Based on the characteristics of the respondents, the maximum age was 22 years. Bivariate results show that there is an influence of butterfly hug therapy on the level of anxiety in preparing theses among nursing students at Awal Bros University with an average difference before and after butterfly hug therapy of 15.4 with a P-Value of 0.000 (<0.05) . It was concluded that there was an influence of butterfly hug therapy on the level of anxiety in preparing theses among nursing students at Awal Bros University. It is hoped that these students will be able to apply butterfly hug therapy to reduce anxiety when preparing their thesis.